2017
DOI: 10.1021/acs.jpclett.7b01810
|View full text |Cite
|
Sign up to set email alerts
|

Thioamide, a Hydrogen Bond Acceptor in Proteins and Nucleic Acids

Abstract: Thioamides are used as potential surrogates of amides to study the structure and dynamics of proteins and nucleic acids. However, incorporation of thioamides in biomolecules leads to changes in their structures and conformations mostly attributed to the strength of the amide-N-H···S═C hydrogen bond. In most cases, it is considered weak owing to the small electronegativity of sulfur, and in some cases, it is as strong as conventional H-bonds. Herein, adopting PDB structure analysis, NMR spectroscopy, and quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 59 publications
(83 reference statements)
1
55
0
Order By: Relevance
“…25 Studies on small peptide systems have revealed that backbone-backbone H-bonding interactions may exist in thioamides. 26,27 Nonetheless, it was generally assumed for some time that a side-chain thioether was a poor H-bond acceptor and that N-H/S interactions between amide backbones and the sulfur atom of methionine were weak and of little signicance. 28,29 Recent observations on model systems have challenged this credo, however.…”
Section: Introductionmentioning
confidence: 99%
“…25 Studies on small peptide systems have revealed that backbone-backbone H-bonding interactions may exist in thioamides. 26,27 Nonetheless, it was generally assumed for some time that a side-chain thioether was a poor H-bond acceptor and that N-H/S interactions between amide backbones and the sulfur atom of methionine were weak and of little signicance. 28,29 Recent observations on model systems have challenged this credo, however.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, it has become evident that the replacement of oxygen in amide bonds by other chalcogens such as sulphur and selenium retains the ability of the resulting thio-and selenoamides to engage in hydrogen bonding interactions. [17][18][19][20] In addition, it has been observed both theoretically and experimentally that NHÁ Á ÁS or NHÁ Á ÁSe hydrogen bonds can be as strong as those of NHÁ Á ÁO, despite the lower electronegativity of S and Se. 21,22 In proteins and peptides, the introduction of thioamide or selenoamide bonds has allowed to tune their structure, stability, and -in case of enzymes -activity.…”
mentioning
confidence: 99%
“…Here, we disclose the synthesis (reported in the ESI †) and selfassembly of the chiral, C 3 -symmetrical benzene-tricarboselenoamide c-SeBTA (Scheme 1). We compare its self-assembly behavior to that of OBTA/c-OBTA 20 and SBTA/c-SBTA. 21 The different nature of the selenoamide hydrogen bond is illustrated by our finding that c-SeBTA polymers have an increased stability towards thermal denaturation yet enhanced lability towards polar solventsinduced denaturation.…”
mentioning
confidence: 99%
“…The substitution of O with S provides a greater contact surface area between the peptide and the receptor, which leads to improved van der Waals interactions mediated by the C S group compared to the C O group. 10 Although we did not notice any direct hydrogen bonds between the protein and S atom, 31 we cannot fully negate the possibility of any water mediated hydrogen bonding between the S atom and the receptor. 32 …”
Section: Resultsmentioning
confidence: 66%